2001
DOI: 10.1089/104303401750148702
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Function and Transgene Expression in the Guinea Pig Cochlea, Using Adenovirus- and Adeno-Associated Virus-Directed Gene Transfer

Abstract: Development of a viral vector that can infect hair cells of the cochlea without producing viral-associated ototoxic effects is crucial for utilizing gene replacement therapy as a treatment for certain forms of hereditary deafness. In the present study, cochlear function was monitored using distortion-product otoacoustic emissions (DPOAEs) in guinea pigs that received infusions of either (E1(-), E3(-)) adenovirus, or adeno-associated virus (AAV), directly into the scala tympani. Replication-deficient (E1(-), E3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 22 publications
1
64
0
Order By: Relevance
“…Indeed, gene expression in the sensory hair cells and strial cells has previously been reported using the same syringe inoculation protocol. 10 Intriguing, however, are the results of Luebke et al, 8,9 who reported that 7 days of delivery of adenovirus into the basal turn perilymph via an osmotic minipump led to preservation of hearing and b-gal expression specifically in the sensory hair cells, but not into the adjacent structures such as the supporting cells. In Accordance with Ishimoto et al, 6 who was unable to replicate this result, we suggest that the method used to detect b-gal expression may account for this unexpected result.…”
Section: Efficiency and Safety Of Gene Transfer In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, gene expression in the sensory hair cells and strial cells has previously been reported using the same syringe inoculation protocol. 10 Intriguing, however, are the results of Luebke et al, 8,9 who reported that 7 days of delivery of adenovirus into the basal turn perilymph via an osmotic minipump led to preservation of hearing and b-gal expression specifically in the sensory hair cells, but not into the adjacent structures such as the supporting cells. In Accordance with Ishimoto et al, 6 who was unable to replicate this result, we suggest that the method used to detect b-gal expression may account for this unexpected result.…”
Section: Efficiency and Safety Of Gene Transfer In Vivomentioning
confidence: 99%
“…6,7 However, other studies have demonstrated that adenovirus vectors can indeed transduce sensory hair cells in the organ of Corti. [8][9][10] So far, no explanation has been provided to explain this discrepancy.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] HSV, vaccina virus, lentivirus, and AAV vectors have also failed to infect cochlear hair cells when tested in vivo. [7][8][9] Interestingly, replication-deficient adenoviral vectors (ie E1 − , E3 − ), using the Rous sarcoma virus (RSV) promoter to drive LacZ expression, have failed to transduce cochlear hair cells in vivo when approximately 10 7 plaque-forming units of virus were injected into scala tympani. 10 In addition, the studies using adenoviral constructs to infect cochlea cells in vivo, either did not assess cochlea function, or used a functional test (ie auditory brainstem response or ABR) that evaluated principally the ascending auditory system at the auditory nerve and brainstem level, thus, only grossly examined hair cell function.…”
Section: Introductionmentioning
confidence: 99%
“…38 AAV vectors can accommodate DNA of 3.5-4.0 kilobases (kb), 18 sufficient to accommodate the DNA (o3 kb) encoding cytokines and neurotrophins. 37 AAV vectors are less toxic than Ad vectors, 39 although damage to cochlear architecture has been observed in a 24-day study. 31 Like Ad vectors, there is variation in expression profiles among experiments.…”
Section: Adeno-associated Viralmentioning
confidence: 99%